Measurement of nitric oxide from cigarette burning using TDLAS based on quantum cascade laser. (April 2020) - Zheng, Fei; Qiu, Xuanbing; Shao, Ligang; Feng, Shiling; Cheng, Tong; He, Xiaohu; He, Qiusheng; Li, Chuanliang; Kan, Ruifeng; Fittschen, Christa
Highlights: A continuous DFB-QCL is first used in TDLAS for measuring emitted NO of cigarette. High dynamic response of system is achieved due to a low volume absorption cell. An adaptive Kalman filter is employed to reduce the concentration measurement noise. Emitted NO masses of cigarette smoke are determined at deferent burning behaviors. Abstract: Nitric oxide (NO) is an important product released by cigarette burning with significantly negative effects to both environment and human health, but it is hard to be measured in-situ in the process of burning. In this paper, we report a tunable diode laser absorption spectroscopy (TDLAS) set-up using a quantum cascade laser emitting at 5.24 μ m to continuously determine the emitted NO mass in cigarette smoke during burning. Wavelength modulation spectroscopy was applied to improve the detection sensitivity and robustness of the measurement system. A simple single-pass gas cell with a volume of 28 cm 3 was used to record the absorption spectra, and then the mass of NO was derived based on the measured line strength. Allan variance analysis demonstrated that the limit of detection of system reached 28 ppb over 180 s integration time. Due to the low effective volume, the rise time and the fall time were rapid with 3 s and 6 s, respectively. An adaptive Kalman filter was used to reduce the noise on the concentration measurement. As a result, the measurement precision is improved by a factor of 4.5. For accurate determination the total NO mass, the emissions of mainstream (MS) and sidestream (SS) of a burning cigarette were individually measured at the same continuous flow rate. The recorded results of three types of cigarettes revealed that the NO mass emitted in the MS is correlated with the sampling flow rate, while the NO mass emitted by the same cigarette in the SS is hardly influenced by at different smoke flow rates. And different cigarette types with identical physical dimensions emit approximately equivalent mass of NO. This work provides a promising method for determining the mass of emitted NO and other compositions of cigarettes smoke.